English for Administration: Enhancing Government Employees’ Communication Skills - Setiyo Wahyuni, Elli; Rachman, Cyril Bernard (JEES (Journal of English Educators Society), 2024)
Excellent public service requires government employees to possess professional skills, one of which is proficiency in English communication. This study explores how tourism and hospitality training can enhance employees’ ability to interact with foreign visitors at tourism destinations. The study utilizes observation, role-playing, and focus group discussion as primary methods, involving 40 government employees in a program designed to develop effective communication skills for interacting with tourists. The findings highlight comm unication challenges faced by the community as it aims to establish itself as an international tourism destination. The findings indicate that role-playing is particularly effective in simulating real- world interactions, helping participants understand how to communicate in practical situations. Furthermore, focus group discussions provide insight into the participants’ views on the training program. The study concludes that English for administration enhances the employees’ communication with visitors, equipping them with effective and appropriate techniques for welcoming and guiding tourists. This contributes to improved service quality and better understanding of hospitality practices, enabling the community to become more skilled and professional. The study also suggests that improving speaking skills requires multiple approaches, including teaching methods tailored to the participant’s needs and the use ofauthentic materials. Future research should investigate the government employees’ competencies in reading, listening, and writing skills. Furthermore, the study underscores the correlation between public service excellence and the quality of the workforce. HIGHLIGHTS: English for public service is suitable knowledge to improve governmentemployees’ communication skill. Role playing is an effective learning method to practice conversation withforeigners. Speaking in English should be enhanced to promote tourism objects at Setigi forInternational recognition.